Age-Dependency of Location of Epileptic Foci in “Continuous Spike-and-Waves during Sleep”: A Parallel to the Posterior-Anterior Trajectory of Slow Wave Activity - Heinzle, Bigna Katrin Bölsterli; Bast, Thomas; Critelli, Hanne; Huber, Reto; Schmitt, Bernhard (Neuropediatrics, 2017)
Background Epileptic encephalopathy with continuous spike-and-waves during sleep (CSWS) occurs during childhood and is characterized by an activation of spike wave complexes during slow wave sleep. The location of epileptic foci is variable, as is etiology. A relationship between the epileptic focus and age has been shown in various focal epilepsies following a posterior-anterior trajectory, and a link to brain maturation has been proposed.We hypothesize that in CSWS, maximal spike wave activity, corresponding to the epileptic focus, is related to age and shows a posterior-anterior evolution.Findings In a retrospective cross-sectional study on CSWS (22 EEGs of 22 patients aged 3.1–13.5 years), the location of the epileptic focus is related to age and follows a posterior-anterior course. Younger patients are more likely to have posterior foci than older ones.Conclusions We propose that the posterior-anterior trajectory of maximal spike waves in CSWS might reflect maturational changes of maximal expression of sleep slow waves, which follow a comparable course. Epileptic spike waves, that is, “hyper-synchronized slow waves” may occur at the place where the highest and therefore most synchronized slow waves meet brain tissue with an increased susceptibility to synchronization.
Keywords: CSWS; ESES; sleep; slow waves; epileptic focus; brain maturation